2012
DOI: 10.1021/nn302235u
|View full text |Cite
|
Sign up to set email alerts
|

Cerium Dioxide Nanoparticles Induce Apoptosis and Autophagy in Human Peripheral Blood Monocytes

Abstract: Cerium dioxide nanoparticles (CeO2 NPs) have diversified industrial uses and novel therapeutic applications are actively being pursued. There is lack of mechanistic data concerning the effects of CeO2 NPs on primary human cells. We aimed at characterizing the cytotoxic effects of CeO2 NPs in human peripheral blood monocytes. CeO2 NPs and their suspensions were thoroughly characterized, including using transmission electron microscopy (TEM), dynamic light scattering (DLS), and zeta potential analysis. Blood fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
154
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(166 citation statements)
references
References 43 publications
(72 reference statements)
9
154
2
1
Order By: Relevance
“…9 However, several reports suggested that the uptake of CeONP could induce oxidative stress and DNA damage, dephosphorylation of various substrates, aberrant cell signaling and alterations in the transcriptional and posttranslational levels. [109][110][111] The cell lines used in the published studies established cell lines and primary cultures from tumors or normal tissues, which has been thoroughly reviewed in the literature. Although it was recently demonstrated that localization of CeONP in acidified lysosomes induced cell death 111 and that CeONP could induce cytotoxicity through autophagy and a mitochondrial apoptosis pathway, 110 simple correlations of the cytotoxicity effect of CeONP with cell types or particle size/preparations has not been established.…”
Section: The Toxicological Effects Of Ceonpmentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, several reports suggested that the uptake of CeONP could induce oxidative stress and DNA damage, dephosphorylation of various substrates, aberrant cell signaling and alterations in the transcriptional and posttranslational levels. [109][110][111] The cell lines used in the published studies established cell lines and primary cultures from tumors or normal tissues, which has been thoroughly reviewed in the literature. Although it was recently demonstrated that localization of CeONP in acidified lysosomes induced cell death 111 and that CeONP could induce cytotoxicity through autophagy and a mitochondrial apoptosis pathway, 110 simple correlations of the cytotoxicity effect of CeONP with cell types or particle size/preparations has not been established.…”
Section: The Toxicological Effects Of Ceonpmentioning
confidence: 99%
“…[109][110][111] The cell lines used in the published studies established cell lines and primary cultures from tumors or normal tissues, which has been thoroughly reviewed in the literature. Although it was recently demonstrated that localization of CeONP in acidified lysosomes induced cell death 111 and that CeONP could induce cytotoxicity through autophagy and a mitochondrial apoptosis pathway, 110 simple correlations of the cytotoxicity effect of CeONP with cell types or particle size/preparations has not been established. 112 In vivo studies In vivo analyses of the biological effect of CeONP were carried out by peroral, intravenous or intraperitoneal administration to laboratory animals.…”
Section: The Toxicological Effects Of Ceonpmentioning
confidence: 99%
“…Hussain et al [46] suggested many possible toxic effects of ceria on human peripheral blood monocytes. In their ex vivo study, they first observed an up-regulation in autophagy caused by an inhibition of p53 proteins, which are the proteins that regulate the cell cycle and prevent cancer formation, leading to cell death.…”
Section: Toxicity Of Nanoceriamentioning
confidence: 99%
“…Target molecules for NSAIDs that participate at signaling pathways, include: 15-lipoxygenase-1, peroxisome proliferator-activated receptors (PPARs), P 21 ras signaling and AKT/PKB kinase (19)(20)(21). Cerium oxide nanoparticles induced apoptosis and autophagy in human peripheral blood monocytes (22). Doxorubicin nanoparticles have the potential to serve as a beneficial healing approach to overcome the chemoresistance of adriamycin-resistant breast cancer (23).…”
Section: Introductionmentioning
confidence: 99%